The Role of Halal Awareness on the Relationship between Religiosity and Halal Purchase Intention - Albra, Wahyuddin; Muchtar, Darmawati; Nurlela, Nurlela; Muliani, Muliani; Safitri, Risna; Nisa, Fitria Zaitun (International Journal of Islamic Economics and Finance (IJIEF), 2023)
This study aims to investigate the effect of religiosity and halal awareness on halal purchase intention and analyze the mediating effect of halal awareness on the relationship between religiosity and halal purchase intention. The cluster sampling method was employed to select the sample size, and the total sample was 400 respondents from three regions of Aceh Province. This study used Structure Equation Modeling (SEM) AMOS to predict a set of indicators of latent variables constructed by several dimensions and indicators, i.e., religiosity was measured by ritual, ideology, intellectual, passion, and consequential dimensions, while halal awareness was determined by five indicators, as well as halal purchase intention. The validity and reliability were tested, and all the latent constructs had a good discriminant validity value. Additionally, the full model after modification was utilized to raise the Goodness of Fit (GOF). The results demonstrated that religiosity positively and significantly affected halal awareness. Similarly, religiosity and halal awareness positively and significantly affected halal purchase intention. It indicates that increasing religiosity and halal awareness enhance interest in buying halal food. It can be concluded that religiosity and awareness are vital indicators in explaining the increasing interest in buying halal products. Moreover, the mediating effect results uncovered a partial mediation of halal awareness on the relationship between religiosity and halal purchase intention. It implies that halal awareness has an essential role in mediating this relationship.